Design of Polyether sulfone flat-sheet membranes for multi-layered hemodiafiltration devices - Rei Kono; Takashi Ota; Yoshihiko Kanno; Norihisa Miki (PLoS ONE, 2025)
Multilayered hemodialysis devices enable blood flow without the need for an external pump, whereas hollow fiber-type devices require a pump due to significant pressure loss across the fibers. This highlights a key advantage of multilayered devices for implantable applications, where a simpler and lighter system reduces the burden on patients. This study investigates the mechanical strength and dialysis efficiency of polyether sulfone (PES) flat-sheet membranes for multilayered devices. PES membranes, with thicknesses ranging from 40 to 160 µm, were prepared using the liquid inversion method, with thickness controlled via spin coating. The mechanical strength of the membranes was tested following the ISO 8637–1:2017 protocol, and membranes thicker than 80 µm were experimentally verified to withstand pressures of up to 500 mmHg, making them suitable for dialysis applications. Furthermore, the study demonstrates the successful use of 80 µm membranes in both in vitro and ex vivo experiments with rats, identifying this thickness as optimal for multilayered dialysis devices.